Coelho, Victor and Keith Polk. 2016. Instrumentalists and Renaissance Culture, 1420-1600: Players of Function and Fantasy. Cambridge: Cambridge University Press. - Ligrani, Jonathan (Current Musicology, 2019)
Instrumental music permeated the soundscape of Renaissance Europe, resounding from watchtowers and ceremonial processions, echoing from the walls of castles and cathedrals, directing the steps and competing with the din of dancers’ shuffling feet, and occupying the intervals between theatrical acts and the courses of patricians’ daily banquets. Despite the ubiquity and significance of these sounds, musicologists have overlooked their presence in the landscape of Renaissance scholarship.